Formación con perspectiva de género, una tarea pendiente El caso de los asuntos de alimentos tramitados por el Consultorio Jurídico de la Universidad de Antioquia, Medellín - Cardona Zuleta, Elvigia (Universidad Católica Luis Amigó, 2021)
This book presents a theoretical and methodological proposal that provides pedagogical and didactic elements for the training of undergraduate law students, from a Gender Equity Approach for Women (EEGM). The research from which it derives reveals the stereotypes associated with the issue of alimony obligations present in students and professors, and highlights the importance of intercultural, intersectional and differentiated practices in the attention to the users of alimony claims that are processed in the Guillermo Peña Alzate Legal Clinic of the Faculty of Law and Political Sciences of the University of Antioquia, Medellin, with the purpose that the student, in his stage of academic practices, can use different theoretical, conventional, jurisprudential and normative instruments, framed in the cultural studies of law.